2020
DOI: 10.1186/s40635-019-0291-9
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of targeted temperature management in animal models of cardiac arrest

Abstract: Background: Targeted temperature management (TTM) of 32 to 34°C has been the standard treatment for out-of-hospital cardiac arrest since clinical trials in 2002 indicated benefit on survival and neurological outcome. In 2013, a clinical trial showed no difference in outcome between TTM of 33°C and TTM of 36°C. In this meta-analysis, we investigate the evidence for TTM in animal models of cardiac arrest. Methods: We searched PubMed and EMBASE for adult animal studies using TTM as a treatment in different models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 82 publications
1
41
0
4
Order By: Relevance
“…We are aware of one other systematic review and meta-analysis on this topic, which partly overlaps with our aim of the study. Olai and colleagues 18 applied more broad eligibility criteria including models of global and local brain ischaemia without cardiac arrest, target temperatures below 32 C, induced pre-arrest, intra-arrest as well as post-arrest, TTM by cardiopulmonary bypass systems, and brain histology as outcome parameter. While this may be a comprehensive approach, comparability to the clinical cardiac arrest studies may be difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware of one other systematic review and meta-analysis on this topic, which partly overlaps with our aim of the study. Olai and colleagues 18 applied more broad eligibility criteria including models of global and local brain ischaemia without cardiac arrest, target temperatures below 32 C, induced pre-arrest, intra-arrest as well as post-arrest, TTM by cardiopulmonary bypass systems, and brain histology as outcome parameter. While this may be a comprehensive approach, comparability to the clinical cardiac arrest studies may be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal studies on the efficacy of cooling exist, and previous reviews have either summarised articles concerning intra-arrest hypothermia, 17 or assessed the pooled efficacy of pre-arrest, intra-arrest, and post-arrest hypothermia and hypothermia in various brain ischaemia models. 18 However, no systematic review has either analysed the pooled effects of TTM in a clinically relevant cardiac arrest model with post-arrest induction of mild hypothermia, or has examined multiple effect modifiers in a metaregression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The only therapeutic intervention that has shown some benefits to mitigate the sequelae of HIBI is the use of targeted temperature management (TTM); at this moment, three randomized clinical trials (RCTs) have demonstrated a significant improvement in the proportion of patients with favorable neurological outcome when cooling at 33 °C for 24 h was compared to no temperature control or normothermia [ 5 , 6 , 7 ]. Nevertheless, although TTM remains still recommended into international guidelines [ 8 ], the level of evidence supporting its use remains low (because of several methodological bias present into initial trials [ 5 , 6 ]), many concerns on clinically relevant effectiveness have been raised also for experimental studies [ 9 ] and a large trial has been recently completed (NCT03114033) and will eventually provide a definitive answer on the role of TTM in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic hypothermia or hypothermic targeted temperature management (HTTM, 32–36 °C) has emerged as a proven strategy to minimize secondary brain damage in survivors of CA and has become the recommended treatment by the American Heart Association [ 4 ]. Hypothermia protects against CA- and resuscitation-induced brain injury and improves neurological outcome in CA patients and animals [ 5 , 6 ]; these effects are multifactorial and may involve in the inhibition of inflammatory reactions, decrease in oxidative stress, attenuation of blood–brain barrier disruption, and inhibition of early brain edema [ 7 9 ]. However, the precise mechanism of this protection is largely unknown.…”
Section: Introductionmentioning
confidence: 99%